Effects of Resin Refining on the Chemical and Physical Stability of Sardine Oils - Hari Eko Irianto (Indonesian Food and Nutrition Progress, 1994)
The effect of resin refining on the stability of sardine oil was studied. Fish canning waste oil and fish meal processing waste oil were used in the experiment. The oils were refined by passing through the resin packed column at fish oil and resin ration of 1 : 1.            The fish oil stability was investigated using Schaal oven method by placing the oil in an oven at 63 ± 2oC and the sample was withdrawn after 0, 2, 4, 7 and 11 days. Resin refining improved fish oil quality as indicated by lower FFA value and brighter colour, this process reduced natural antioxidant content. Results of stability test indicated that refined oil had a lower stability than unrefined oil by showing a higer rate of peroxide value, TBA value, anisidine value and totox value increases as well as colour absorbance decrease. Meanwhile, canning waste oil exhibited a lower stability compared to fish meal processing waste oil.